Not a completely happy ending - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Montpellier Forum on Rural Development Cooperation, held in France in early September 2002, brought together 200 European rural development and livelihood specialists, and a good number of Southern partners from Africa, Asia and the Americas....